A national population‐based cohort study to investigate inequalities in maternal mortality in the United Kingdom, 2009‐17. Issue 4 (3rd February 2020) - Knight, Marian; Bunch, Kathryn; Kenyon, Sara; Tuffnell, Derek; Kurinczuk, Jennifer J.
Abstract: Background: Disparities have been documented in maternal mortality rates between women from different ethnic, age and socio‐economic groups in the UK. It is unclear whether there are differential changes in these rates amongst women from different groups over time. The objectives of this analysis were to describe UK maternal mortality rates in different age, ethnic and socio‐economic groups between 2009 and 2017, and to identify whether there were changes in the observed inequalities, or different trends amongst population subgroups. Methods: Maternal mortality rates with 95% confidence intervals (CI) in specific age, deprivation and ethnic groups were calculated using numbers of maternal deaths as numerator and total maternities as denominator. Relative risks (RR) with 95% CI were calculated and compared using ratios of relative risk. Change over time was investigated using non‐parametric tests for trend across ordered groups. Results: Women from black and Asian groups had a higher mortality rate than white women in most time periods, as did women aged 35 and over and women from the most deprived quintile areas of residence. There was evidence of an increasing trend in maternal mortality amongst black women and a decrease in mortality amongst women from the least deprived areas, but no trends over time in any of the other ethnic, age or IMD groups were seen. There was a widening of the disparity between black and white women (RR 2.59 in 2009‐11 compared with 5.27 in 2015‐17, ratio of the relative risks 2.03, 95% CI 1.11, 3.72). Conclusions: The clear differences in the patterns of maternal mortality amongst different ethnic, age and socio‐economic groups emphasise the importance of research and policies focussed specifically on women from black and minority ethnic groups, together with other disadvantaged groups, to begin to reduce maternal mortality in the UK.